1998
DOI: 10.1615/critrevneurobiol.v12.i4.40
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models of Alcoholism: Neurobiology of High Alcohol-Drinking Behavior in Rodents

Abstract: This review discusses efforts to develop rodent models for the study of neurobiological mechanisms underlying chronic alcohol drinking, alcoholism, and abnormal alcohol-seeking behavior. Selective breeding has produced stable lines of rats that reliably exhibit high and (for comparison purposes) low voluntary alcohol consumption. In addition, animal models of chronic ethanol self-administration have been developed in rodents, who do not have a genetic predisposition for high alcohol-seeking behavior, to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
454
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 578 publications
(472 citation statements)
references
References 0 publications
17
454
0
1
Order By: Relevance
“…In the previous studies, we have found that 15 non-contingent presentations of the alcohol-associated stimulus complex produced immediate reinstatement of alcohol-seeking behavior (eg Bienkowski et al, 2000). In aggregate, our behavioral observations confirm that both alcohol-paired context and discrete cues may have incentive motivational properties for rats with alcohol self-administration history (McBride and Li, 1998;Le and Shaham, 2002;McBride et al, 2002).…”
Section: Pattern Of C-fos Activation In the Amygdala: A Role In Plastsupporting
confidence: 82%
“…In the previous studies, we have found that 15 non-contingent presentations of the alcohol-associated stimulus complex produced immediate reinstatement of alcohol-seeking behavior (eg Bienkowski et al, 2000). In aggregate, our behavioral observations confirm that both alcohol-paired context and discrete cues may have incentive motivational properties for rats with alcohol self-administration history (McBride and Li, 1998;Le and Shaham, 2002;McBride et al, 2002).…”
Section: Pattern Of C-fos Activation In the Amygdala: A Role In Plastsupporting
confidence: 82%
“…The animals selectively bred for excessive drinking show many of the characteristics of human alcoholics such as high alcohol intake, a generalized decreased sensitivity to alcohol, and drinking to the point of showing withdrawal effects upon cessation of drinking (McBride and Li 1998). Studies with inbred strains of mice allow for crossing and the identification of specific gene loci linked to a given trait by use of quantitative trait locus analysis (Phillips et al 1994).…”
Section: Animal Genetic Studiesmentioning
confidence: 99%
“…Animal models based on selective breeding for excessive ethanol drinking have demonstrated a utility for identifying and validating novel alcoholism treatment targets (McBride and Li, 1998). The alcohol-preferring AA (Alko Alcohol) and the alcohol-avoiding ANA (Alko Non-Alcohol) rat lines are among the best-established selection-based models, and have been bidrectionally bred for high and low alcohol consumption, respectively, for over 90 generations (Sinclair et al, 1989).…”
Section: Introductionmentioning
confidence: 99%